The effect of mental accounting in the luxury market: prepared and unprepared consumers - Dong Hyun Son; Dongwoo Ko; Ji-yeon Lee (Frontiers in Psychology)
IntroductionSocial networking sites (SNSs) are increasingly influencing consumer behavior and attitudes toward luxury consumption by fostering social comparison and perceived inequality.MethodsWe conducted a survey with 320 U.S.-based participants through Amazon Mechanical Turk. Measures included SNS usage, subjective inequality, mental accounting, and luxury attitude. Hayes' PROCESS macro (Model 15) was used for moderated mediation analysis.ResultsSNS usage significantly increased luxury attitude directly and indirectly through subjective inequality. Mental accounting moderated both the direct and indirect effects: high mental accounting weakened the direct effect but amplified the indirect effect via inequality.DiscussionThese findings suggest that mental accounting acts both as a self-regulatory buffer and a justification mechanism in luxury consumption. The study highlights the psychological pathway through which SNS usage influences luxury attitude and offers theoretical and practical implications for consumer behavior research.